Six-Minute Walk Test as a Discharge Criterion and Predictor of Three-Month Readmission in Pulmonary Medicine Patients - Shrestha, Sanjeet Krishna; Poudel, Saroj; Lama, Rakesh; Giri, Rashmi; Karthak, Ashish; Gurung, Naresh; Singh, Summer J; Bhattarai, Sanjeet (Nepalese Respiratory Journal, 2025)
Background: The six-minute walk test (6MWT) is a commonly used tool for measuring functional capacity and predicting outcomes in respiratory disease patients. Objective: To determine the three-month readmission rate among patients who have completed and those who have not completed the 6MWT at hospital discharge. Methods: A prospective observational study was carried out at a tertiary care hospital between June and August 2024 with, 250 respiratory disease patients admitted through the Emergency Department or OPD to the respiratory ward. All patients received a 6MWT before discharge, per ATS guidelines, which measures six-minute walk distance (6MWD), oxygen supplementation, and Borg scale scores for dyspnea and fatigue. Readmission was monitored for three-month periods through OPD visits. Results: Out of 250 patients, the mean age was 65.2 ± 14.0 years, and 46.8% were male. 80.4% of patients passed the test, and 19.6% failed. Oxygen supplementation was required by 28.8%, with comparable pass rates in both groups. The three-month readmission rate was 12.4%, with significantly higher odds among those patients who failed (34.7%, OR=6.94) versus those who passed (7.0%). Patients walking less than 300 meters had a 4.52-fold higher readmission risk, an each 100-meter increase in 6MWT reduced odds by 20 (OR=0.8). Most patients reported minimal dyspnea (49.2%) and fatigue (44.4%). Conclusion: The 6MWT served as an important assessment for the functional capacity of patients with respiratory disease. Failure to complete the test (OR=6.94) or walking less than 300 meters (OR=4.52) considerably increased the risk of readmission. The test is, therefore, a useful predictor for determining readmission risk and discharge criteria. Further research is required to explore interventions that will enhance the functional capacity and prevent readmission.